Gene mutation discovery research of non-smoking lung cancer patients due to indoor radon exposure. Issue 1 (December 2016) - Choi, Jung; Park, Seong; Noh, O; Koh, Young; Kang, Dae
Abstract Although the incidence and mortality for most cancers such as lung and colon are decreasing in several countries, they are increasing in several developed countries because of an unhealthy western lifestyles including smoking, physical inactivity and consumption of calorie-dense food. The incidences for lung and colon cancers in a few of these countries have already exceeded those in the United States and other western countries. Among them, lung cancer is the main cause of cancer death in worldwide. The cumulative survival rate at five years differs between 13 and 21 % in several countries. Although the most important risk factors are smoking for lung cancer, however, the increased incidence of lung cancer in never smokers(LCINS) is necessary to improve knowledge concerning other risk factors. Environmental factors and genetic susceptibility are also thought to contribute to lung cancer risk. Patients with lung adenocarcinoma who have never smoking frequently contain mutation within tyrosine kinase domain of the epidermal growth factor receptor(EGFR) gene. Also, K-ras mutations are more common in individuals with a history of smoking use and are related with resistance to EFGR-tyrosine kinase inhibitors. Recently, radon(Rn), natural and noble gas, has been recognized as second common reason of lung cancer. In this review, we aim to know whether residential radon is associated with an increased risk for developing lung cancer and regulated by several genetic polymorphisms.